Passing interest : racial passing in US novels, memoirs, television, and film, 1990-2010 - Nerad, Julie, 1969- (Albany, NY : SUNY Press, 2014)
"The first volume to focus on the trope of racial passing in novels, memoirs, television, and films published or produced between 1990 and 2010, Passing Interest takes the scholarly conversation on passing into the twenty-first century. With contributors working in the fields of African American studies, American studies, cultural studies, film studies, literature, and media studies, this book offers a rich, interdisciplinary survey of critical approaches to a broad range of contemporary passing texts. Contributors frame recent passing texts with a wide array of cultural discourses, including immigration law, the Post-Soul Aesthetic, contemporary political satire, affirmative action, the paradoxes of "colorblindness," and the rhetoric of "post-racialism"--
Introduction: The (not so) new face of America / Julie Cary Nerad -- On the margins of a movement: passing in three contemporary memoirs / Irina Negrea -- "A cousin to blackness": race and identity in Bliss Broyard's One drop: My father's hidden life / Lynn Washington and Julie Cary Nerad -- Can one really choose?: passing and self-identification at the turn of the 21st century / Jené Schoenfeld -- Passing in blackface: the intimate drama of post-racialism on Black. White. / Eden Osucha -- Broke right in half: racial passing of/in Alice Randall's The wind done gone / Julie Cary Nerad -- Passing for Chicano, passing for White: negotiating Filipino American identity in Brian Ascalon Roley's American son / Amanda Page -- Race in the Marketplace: Postmodern Passing and Ali G / Ana Mendes -- Passing for Black, White, and Jewish: mixed race identity in Rebecca Walker and Danzy Senna / Lori Harrison-Kahan -- Smiling faces: Chameleon Street, racial passing/performativity, and film blackness / Michael B. Gillespie -- Consuming performances: race, media, and the failure of the cultural mulatto in Bamboozled and Erasure / Meredith McCarroll.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Andrae, A; Bibel; Universidad Sergio Arboleda; American literature -- 20th century -- History and criticism; American literature -- 21st century -- History and criticism; Passing (Identity) -- United States -- History -- 20th century; Passing (Identity) -- United States -- History -- 21st century; Passing (Identity) in literature; Passing (Identity) in motion pictures; Race in literature; Race in motion pictures; Littérature américaine -- 20e siècle -- Histoire et critique; Littérature américaine -- 21e siècle -- Histoire et critique; Passing (Identité) -- États-Unis -- Histoire -- 20e siècle.; Passing (Identité) -- États-Unis -- Histoire -- 21e siècle.; Passing (Identité) dans la littérature.; Race dans la littérature.; Race au cinéma.; LITERARY CRITICISM -- American -- General; American literature; Passing (Identity); Passing (Identity) in literature; Passing (Identity) in motion pictures; Race in literature; Race in motion pictures; United States; Autobiografie; Amerikanisches Englisch; Fernsehsendung; Rasse; Verwechslung; LITERARY CRITICISM / American / General; 1900-2099; Criticism, interpretation, etc; History